Điều kiện tự làmtanx(tanx−tan3x)=2⇔sinx(sinx.cos3x−sin3x.cosx)=2cos2x.cos3x⇔sinx.sin(−2x)=2cos2x.cos3x⇔−2sin2x.cosx=2cos2xcos3x$\Leftrightarrow sin^2x = cosx.cos3x$$\Leftrightarrow -\dfrac{1}{2}(1 - cos2x) = \dfrac{1}{2}(cos4x + cos2x) $$\Leftrightarrow cos4x = -1 $ coi như xong
Điều kiện tự làm
tanx(tanx−tan3x)=2⇔sinx(sinx.cos3x−sin3x.cosx)=2cos2x.cos3x⇔sinx.sin(−2x)=2cos2x.cos3x⇔−2sin2x.cosx=2cos2xcos3x$\Leftrightarrow
2sin^2x =
2cosx.cos3x
⇔1−cos2x=cos4x+cos2x\Leftrightarrow
2\cos
^2 2x
+ 2\cos 2x -1
=0$ n
gh
iệm x
ấu ho
ắc